Двоканальна автокомпенсації впливу перешкод на двоступеневий гіроскоп - Ковалец, Ольга Яковлевна (Eastern-European Journal of Enterprise Technologies, 2010)
The estimation of efficiency of method of twochannel is conducted for diminishing of errors of двухстепенных gyroscopes, essence of realization of which consists in the use of two electrically connected gyroscopes. The high-quality and quantitative analysis of influence of the harmonic tossing of object is carried out on the error of measurings